The Progenitor and Early Evolution of the Type IIb SN 2016gkg - Tartaglia L (IOP PUBLISHING LTD, 2022)
We report initial observations and analysis on the Type IIb SN 2016gkg in the nearby galaxy NGC 613. SN. 2016gkg exhibited a clear double-peaked light curve during its early evolution, as evidenced by our intensive photometric follow-up campaign. SN. 2016gkg shows strong similarities with other Type IIb SNe, in particular, with respect to the He I. emission features observed in both the optical and near-infrared. SN. 2016gkg evolved faster than the prototypical Type. IIb SN. 1993J, with a decline similar to that of SN. 2011dh after the first peak. The analysis of archival Hubble Space Telescope images indicate a pre-explosion source at SN. 2016gkg's position, suggesting a progenitor star with a similar to mid-F spectral type and initial mass 15-20 M-circle dot, depending on the distance modulus adopted for NGC. 613. Modeling the temperature evolution within 5 days of explosion, we obtain a progenitor radius of similar to 48-124 R-circle dot, smaller than that obtained from the analysis of the pre-explosion images (240-320 R-circle dot).